Body brokers [videorecording (DVD)] - Swab, John; Kilmer, Jack, 1995-; Williams, Michael Kenneth; Grillo, Frank, 1963-; Leo, Melissa (Lionsgate, 2021)
"The true and untold story of multi-billion-dollar drug and alcohol treatment fraud, where former drug addicts and dealers become millionaires overnight as 'body brokers.'"